Frenkel‐Defect‐Mediated Chemical Ordering Transition in a Li–Mn–Ni Spinel Oxide1. Issue 27 (27th May 2015) - Ryoo, Hyewon; Bae, Hyung Bin; Kim, Young‐Min; Kim, Jin‐Gyu; Lee, Seongsu; Chung, Sung‐Yoon
Abstract Using spinel‐type Li(Mn1.5Ni0.5)O4 with two different cations, Mn and Ni, in the oxygen octahedra as a model system, we show that a cation ordering transition takes place through the formation of Frenkel‐type point defects. A series of experimental results based on atomic‐scale observations and in situ powder diffractions along with ab initio calculations consistently support such defect‐mediated transition behavior. In addition to providing a precise suggestion of the intermediate transient states and the resulting kinetic pathway during the transition between two phases, our findings emphasize the significant role of point defects in ordering transformation of complex oxides.